2004
DOI: 10.1002/anie.200460107
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Mediated Deamination of Cytosine: Experiment and DFT Calculations

Abstract: A mechanism goes platinum: Hydrolytic deamination of cytosine is a major mutagenic event in DNA. Studies with a model system and DFT calculcations demonstrate that deamination is facilitated by coordination of the PtII center to the N3 atom (see scheme; C=cytosine, U=uracil).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
4
36
1
Order By: Relevance
“…The pK a (N(4)H 2 ) of 1 was estimated to be approximately 13.5 in D 2 O, corresponding to ca. 13 in water (see Supporting Information) [16]. 1 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pK a (N(4)H 2 ) of 1 was estimated to be approximately 13.5 in D 2 O, corresponding to ca. 13 in water (see Supporting Information) [16]. 1 …”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that Pt II (1-MeC-N3) complexes undergo cytosine deamination at alkaline pH to the corresponding 1-methyluracilate complexes Pt II (1-MeU-N3) [16]. With (dien)Pt II , a competing reaction takes place, however, in which the metal entity migrates from N3 of cytosine to the exocyclic N4 position (Scheme 1).…”
Section: (Dien)pt II and 1-mec: Metal Migration And Deaminationmentioning
confidence: 96%
See 1 more Smart Citation
“…It is also unusual the situation involv- [35][36][37][38][39][40][41][42][43][44], Pd(II) [45,46] probably due to an initial N3 ! N4 migration of the transition metal [38,47,48]; other cases are (1-MeC-N3)-Cu(II)-(1-MeC-N4) 2 [49], (1-MeC-N3)-Ag(I)-(1-MeC-O2) [13], (1-MeC-N4) 2 -Cu(II)-(1-MeC-O2) 2 [50], and (1-MeC À -N4)-Pd(II)-(1-MeC-O2) [51]. The structure of [Zn 2 (1-MeC-N3) 4 (l-SO 4 ) 2 ] AE H 2 O (2) consists of assembled centrosymmetric dimers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(Cadet & Vigny 1990;Chatgilialoglu et al 2000) Hence, they could act as a trap for a migrating electron hole. (Sponer et al 2004;Yao et al 2005) Unfortunately, however, despite detailed experimental study, the exact route by which such species' (8-oxoB and 8-oxoB • (-H7)) may be formed remains unclear. (Llano & Eriksson 2004b) We performed a computational investigation on the processes by which 8-OHB (aq) may be formed for purine, adenine and guanine.…”
Section: -Oxopurine Formation In Purine Adenine and Guaninementioning
confidence: 99%